Floods, fish, and fishermen - Graaf, Gertjan de. (Dhaka : University Press, 2001)
With reference to Bangladesh.
"Eight years experiences with flood plain fisheries, fish migration, fisheries modelling and fish bio diversity in the Compartmentalization Pilot Project, Bangladesh"--Cover.
Includes bibliographical references.